A Postcard From Italy: Challenges and Psychosocial Resources of Partners Living With and Without a Chronic Disease During COVID-19 Epidemic - Rapelli, Giada; Lopez, Giulia; Donato, Silvia; Pagani, Ariela Francesca; Parise, Miriam; Bertoni, Anna; Iafrate, Raffaella (Frontiers in Psychology, 2020)
The new Coronavirus (COVID-19) has been declared a global pandemic by the World Health Organization (WHO). The sudden outbreak of this new virus and the measure of lockdown adopted to contain the epidemic have profoundly changed the lifestyles of the Italian population, with an impact on people’s quality of life and on their social relationships. In particular, due to forced and prolonged cohabitation, the couple itself may be subject to specific stressors during the epidemic. In addition, all the community was profoundly touched by COVID-19, but living with a chronic health condition may add specific challenges to the ones posed by the epidemic itself. The present cross-sectional study aimed to provide a picture of the challenges as well as the resources for both individual and relational well-being of Italian individuals in a couple relationship (N = 1921), with a specific attention to the comparison of individuals living with and without a chronic disease. Results showed that people with a chronic disease had lower psychological well-being and more fear and worries about the COVID-19. People with a chronic disease perceived fewer resources than the healthy people. Moreover, the challenges are shown to be associated with less psychological well-being and high pessimism about the future. Instead individual, relational and social resources play a protective role during the pandemic for both healthy and people with chronic disease.